"KEBAB NUSANTARA" Kebab Kaya Rasa Nusantara: Inovasi Pangan Lokal Sebagai Alternatif Menu Praktis Berenergi - aryo adhitiowasis; Mohamad Andriansyah; Dewi Tugarini; Caria Ningsih (JURNAL GASTRONOMI INDONESIA, 2022)
Technological changes are very fast in the world media in providing information about various types of food that are very easily accessible to the people of Indonesia, hence the entry of foods from other countries. Making lifestyles and trends today in Indonesian society. By taking the concept of this Turkish Kebab food, it can create new food innovations that can be sold, but it does not eliminate cooking procedures and appearance. The whole manufacturing process uses original food ingredients from Indonesia. Our product innovation is Kebab Nusantara using beef jerky, salad vegetables, cucumber, tomato, mayonnaise sauce, spicy sauce and peanut sauce. Kebab Nusantara uses organoleptic and the nutritional content is calculated. Provide a healthy food for consumption to the people of Indonesia. The price of Nusantara Kebab is Rp. 7000 rupiah, all people can buy because the price is affordable and we use a digital system in orders. The author is not only innovating Kebab Nusantara, but there is a main goal, namely, wanting to provide education to the public to love Indonesian food more. The existence of Nusantara Kebabs among the community makes it more motivation to maintain all Indonesian specialties.